Environmental and Biological Impact of Fly Ash and Metakaolin-Based Alkali-Activated Foams Obtained at 70°C and Fired at 1,000°C - Leonelli, Cristina; Turk, Janez; Poggetto, Giovanni Dal; Catauro, Michelina; Traven, Katja; Mauko Pranjić, Alenka; Ducman, Vilma (Frontiers in Chemistry, 2022)
Alkali-activated foams (AAFs) are inorganic porous materials that can be obtained at temperatures well below 100°C with the use of inorganic wastes as aluminosilicate precursors. In this case, fly ash derived from a Slovenian power plant has been investigated. Despite the environmental benefits per se, due to saving of energy and virgin materials, when using waste materials, it is of extreme importance to also evaluate the potential leaching of heavy metal cations from the alkali-activated foams. This article presents an environmental study of a porous geopolymer derived from this particular fly ash, with respect to the leachability of potentially hazardous elements, its environmental toxicity as determined by biological testing, and the environmental impact of its production. In particular, attention was focused to investigate whether or not 1,000°C-fired alkali-activated fly ash and metakaolin-based foams, cured at 70°C, are environmentally friendlier options compared to unfired ones, and attempts to explain the rationale of the results were done. Eventually, the firing process at 1,000°C, apart from improving technical performance, could reinforce heavy metal cation entrapment within the aluminosilicate matrix. Since technical performance was also modified by addition of different types of activators (K-based or Na-based), as well as by partial replacement of fly ash with metakaolin, a life cycle assessment (LCA) analysis was performed to quantify the effect of these additions and processes (curing at 70°C and firing at 1,000°C) in terms of global warming potential. Selected samples were also evaluated in terms of leaching of potentially deleterious elements as well as for the immobilization effect of firing. The leaching test indicated that none of the alkali-activated material is classified as hazardous, not even the as-received fly ash as component of new AAF. All of the alkali-activated foams do meet the requirements for an inertness. The highest impact on bacterial colonies was found in samples that did not undergo firing procedures, i.e., those that were cured at 70°C, which induced the reduction of bacterial Enterococcus faecalis viability. The second family of bacteria tested, Escherichia coli, appeared more resistant to the alkaline environment (pH = 10–12) generated by the unfired AAMs. Cell viability recorded the lowest value for unfired alkali-activated materials produced from fly ash and K-based activators. Its reticulation is only partial, with the leachate solution appearing to be characterized with the most alkaline pH and with the highest ionic conductivity, i.e., highest number of soluble ions. By LCA, it has been shown that 1) changing K-based activators to Na-based activators increases environmental impact of the alkali-activated foams by 1%–4% in terms of most of the impact categories (taking into account the production stage). However, in terms of impact on abiotic depletion of elements and impact on ozone layer depletion, the increase is relatively more significant (11% and 18%, respectively); 2) replacing some parts of fly ash with metakaolin also results in relatively higher environmental footprint (increase of around 1%–4%, while the impact on abiotic depletion of elements increases by 14%); and finally, 3) firing at 1,000°C contributes significantly to the environmental footprint of alkali-activated foams. In such a case, the footprint increases by around one third, compared to the footprint of alkali-activated foams produced at 70°C. A combination of LCA and leaching/toxicity behavior analysis presents relevant combinations, which can provide information about long-term environmental impact of newly developed waste-based materials.